2018
DOI: 10.3390/pharmaceutics10030080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Red Ginseng Extract on the Pharmacokinetics and Efficacy of Metformin in Streptozotocin-Induced Diabetic Rats

Abstract: The purpose of this study was to investigate the effect of red ginseng extract on the pharmacokinetics (PK) and efficacy of metformin in streptozotocin-induced diabetic rats. The diabetes mellitus rat model was established by intraperitoneally administering multiple doses of streptozotocin (30 mg/kg, twice on day 1 and 8), and diabetic rats received metformin 50 mg/kg with or without single or multiple administration of Korean red ginseng extract (RGE, 2 g/kg/day, once or for 1 week). RGE administration did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The selected RGE dose in this study is in the range of effective dose without significant toxicity and showed similar plasma concentrations of Rb1, Rb2, and Rc (5.3-15.8 nM in rats and 6.2-12.7 nM in human subjects) [19,33]. In numerous animal studies, the RGE dose has ranged from 200 mg/kg to 2.0 g/kg (i.e., 3-15 mg/kg of total ginsenosides) [36,37]. In human studies, RGE was administered to diabetic patients for 4 to 24 weeks at doses of 2.7-6.0g/day, which usually contained 50-100 mg ginsenosides/day [20,38].…”
Section: Discussionsupporting
confidence: 51%
“…The selected RGE dose in this study is in the range of effective dose without significant toxicity and showed similar plasma concentrations of Rb1, Rb2, and Rc (5.3-15.8 nM in rats and 6.2-12.7 nM in human subjects) [19,33]. In numerous animal studies, the RGE dose has ranged from 200 mg/kg to 2.0 g/kg (i.e., 3-15 mg/kg of total ginsenosides) [36,37]. In human studies, RGE was administered to diabetic patients for 4 to 24 weeks at doses of 2.7-6.0g/day, which usually contained 50-100 mg ginsenosides/day [20,38].…”
Section: Discussionsupporting
confidence: 51%
“…Korean red ginseng may benefit mice with streptozotocin-induced diabetes owing to its hypoglycemic and immunomodulatory effects [12]. Supplementation with Korean red ginseng extract (RGE), fermented red ginseng, and black ginseng also has been shown to improve type 1 and type 2 diabetic conditions in both animals [12,13,14] and humans [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The selected RGE dose in this study is in the range that shows anti-diabetic effect. In numerous animal studies that showed anti-diabetic effect of RGE, the RGE dose has ranged from 200 mg/kg to 2.0 g/kg (i.e., 3–15 mg/kg of total ginsenosides) [14,25,26,27]. In human studies, RGE was administered to diabetic patients for 4 to 24 weeks at doses of 2.7 g–6.0g/day, which usually contained 50–100 mg ginsenosides/day [16,17,23].…”
Section: Introductionmentioning
confidence: 99%
“…Group 2 was marked as diabetic control group in which no therapeutic intervention was made throughout the study period. Further, Group 3 was marked as standardtreated group, and this group was treated with metformin as standard drug with a dose of 50 mg kg −1 day −1 (Nam et al, 2018).…”
Section: Introductionmentioning
confidence: 99%